E-098 Human 'Live Cadaver' neurovascular model for proximal and distal mechanical thrombectomy in stroke. (23rd July 2022) - Arturo Larco, J; Irfan Madhani, S; Liu, Y; Abbasi, M; Shahid, A; Mereuta, O; Kadirvel, R; Cloft, H; Kallmes, D; Brinjikji, W; Savastano, L
Abstract : Background and Purpose: Preclinical testing platforms that accurately replicate complex human cerebral vasculature are critical to advance neurointerventional knowledge, tools, and techniques. A more realistic thrombectomy model that can simultaneously and accurately mimic the complex hemodynamics, anatomy and arterial response to thrombectomy devices is largely needed to evaluate and improve thrombectomy devices in the preclinical stage. Here, we introduced and validated a human 'live cadaveric' head-and-neck neurovascular model optimized for proximal and distal vascular occlusion and recanalization techniques. Methods: Human cadaveric head-and-neck specimens were cannulated bilaterally in the jugular veins, carotid, and vertebral arteries. Specimens were then coupled with modular glass models of the aorta and extra-cranial carotid arteries, as well as radial and femoral access ports. Intracranial physiological flow was simulated using a flow-delivery system and blood mimicking fluid. Baseline anatomy, histological and mechanical properties of cerebral arteries were compared to that of fresh specimens. Radiopaque clot analogs were embolized to replicate proximal and distal arterial occlusions, followed by proximal and distal thrombectomy procedures. Experienced interventionalists scored the model on different aspects. The performance of the model was evaluated by semi-quantitative 5-point scale: 5 Equal to patients, 4 Highly realistic, 3 Sufficiently realistic, 2 Not sufficiently realistic, 1 Nonrealistic on aspects such as: anatomy by DSA, fluoroscopic guidance of devices in roadmap, device performance to navigate intracranially, haptic feedback from device manipulation, arterial response to mechanical loading, fluoroscopic appearance of the devices, and overall similarity to patients. Results: Compared to counterpart fresh human arteries, formalin-fixed arteries showed similar mechanical properties, including maximum stretch (1.49±0.09), increased tensile strength/stiffness (1.33±0.26 N/mm), and friction coefficients (0.166 vs 0.155, p=0.16). On histology, mild endothelial loss (<25% of surface) compared with the control was noted in arteries after 3 months of thrombectomy procedures, otherwise the arterial wall maintained the structural integrity. Contrast angiographies showed no micro or macro-vasculature obstruction. Proximal and distal occlusions created within the middle cerebral arteries (MCAs), were consistently obtained and successfully recanalized. Additionally, interventionists scored the model highly realistic, indicating great similarity to patients' vasculature. The Interventionalist feedback of the model were 4.75±0.43 for the anatomy by DSA and roadmap angiography and 4.7±0.45 for all other aspects. Conclusions: The human 'live cadaveric' neurovascular model accurately replicates the anatomy, mechanics and hemodynamics of cerebral vasculature and allows the performance of neurointerventional procedures equivalently to patients. Disclosures: J. Arturo Larco: None. S. Irfan Madhani: None. Y. Liu: None. M. Abbasi: None. A. Shahid: None. O. Mereuta: None. R. Kadirvel: None. H. Cloft: None. D. Kallmes: None. W. Brinjikji: None. L. Savastano: None.